2011
DOI: 10.1007/s11164-011-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of lactic acid into propylene glycol over various metals supported on silica

Abstract: Catalytic hydrogenation of lactic acid to propylene glycol was performed over various metals (Ag, Co, Cu, Ni, Pt, and Ru) supported on silica prepared by an incipient wetness impregnation method. The loading amount of each metal was 5 wt%. Crystallinity of the synthesized catalysts was investigated by X-ray diffraction (XRD), and the BET method was utilized to examine the surface area. Pore volume and pore size of catalysts were determined using BJH analysis of the N 2 adsorption isotherm. Particle sizes of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…This is in line with earlier studies demonstrating that the formation of 1,2-PDO is generally favored at ah igher pressure, [15a] at least in part because of the strong pressure dependency of H 2 solubility in water. [19] The increase of the LA feed concentration five-fold to 0.5 m while keeping the LA/Ru ratio similar to that of the other tests did not affect substantially the reactiono utcome.Asimilar 1,2-PDO yield of 68 %a t 84 %L Ac onversion could be obtained after 4h reactiona t 180 8C. An appropriate amount of spent catalyst was weighed and utilized in an ext catalytic test following the standard procedure (20 mg catalyst, 0.1 m LA).…”
Section: Process Conditions Optimizationmentioning
confidence: 57%
See 3 more Smart Citations
“…This is in line with earlier studies demonstrating that the formation of 1,2-PDO is generally favored at ah igher pressure, [15a] at least in part because of the strong pressure dependency of H 2 solubility in water. [19] The increase of the LA feed concentration five-fold to 0.5 m while keeping the LA/Ru ratio similar to that of the other tests did not affect substantially the reactiono utcome.Asimilar 1,2-PDO yield of 68 %a t 84 %L Ac onversion could be obtained after 4h reactiona t 180 8C. An appropriate amount of spent catalyst was weighed and utilized in an ext catalytic test following the standard procedure (20 mg catalyst, 0.1 m LA).…”
Section: Process Conditions Optimizationmentioning
confidence: 57%
“…It was found that the yield of 1,2‐PDO linearly increases with increasing reaction pressure (Figure S4). This is in line with earlier studies demonstrating that the formation of 1,2‐PDO is generally favored at a higher pressure, at least in part because of the strong pressure dependency of H 2 solubility in water . The increase of the LA feed concentration five‐fold to 0.5 m while keeping the LA/Ru ratio similar to that of the other tests did not affect substantially the reaction outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selectivity to PG reached 90-95% under optimal reaction conditions. Jang et al 10 performed liquidphase catalytic hydrogenation of LA (50 mL, 1 M, 110-170 C, 6-9 MPa) over various metals (Ag, Co, Cu, Ni, Pt and Ru) supported on SiO 2 . Of the catalysts tested, Ru/SiO 2 provided the highest PG yield, which increased with pressure.…”
Section: Introductionmentioning
confidence: 99%